Decoding the Meta Effect of Green Transformational Leadership on Green Creativity Through Subgroup Analysis - Mohapatra, Amiya Kumar; Das, Subhasish; Jha, Shweta; Nayak, Yayati (Prabandhan: Indian Journal of Management, 2025)
Purpose : This study examined the pooled effect of green transformational leadership (GTL) on green creativity (GC) and the effect of organization’s geographical origin on GTL-GC through “meta cum subgroup analysis.” Methodology : This analysis combined the data from 20 independent studies of 5,673 participants. “Meta Essential” tool was used for conducting “meta cum subgroup analysis.” Findings : The overall effect size with a random effects model was a moderate positive correlation (r = 0.44, 95% CI = 0.30 to 0.56), which was statistically significant. But there was very high heterogeneity (I² = 94.82%), indicating very high between-study variance. Geographic region-based subgroup analyses—East Asia, South Asia, and Non-Asia—showed heterogeneity of effect sizes, with South Asia showing the strongest correlation (r = 0.58) and highest heterogeneity (I² = 96.54%). However, between-group differences were statistically not significant (Q = 4.42, p = 0.110), and subgrouping explained only 20.41% of the heterogeneity. A bias analysis of publication using the “Trim and Fill” procedure showed negligible bias, lowering the effect size ever so slightly from z = 0.51 to z = 0.49 by adding one imputed study. Managerial Implications : Keeping the robustness of the findings, managers can frame policies in connection with GTL and GC undoubtedly. However, while the overall findings are strong, the ubiquity of large prediction intervals and large heterogeneity increases the risk of untested moderators. Study-level factors, cultural settings, and methodological quality need to be explored in future studies in order to ascertain sources of variance and maximize the generalizability of findings. Originality : The novelty of this study lies in its integrated “meta cum subgroup analysis” strategy, analyzing not only the general GTL–GC relationship, but also the moderating effect of geographical origin. By taking into account significant heterogeneity and proposing under-explored moderators, it provides novel evidence to encourage future research on green leadership and creativity dynamics.